2015
DOI: 10.1111/cob.12080
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the concept of eating dyscontrol in severely obese patients candidate to bariatric surgery

Abstract: Eating dyscontrol constitutes a potential negative predictor for the outcome of treatment strategies for obese patients. The aim of this study was to examine the qualitative characteristics of eating dyscontrol in obese patients who engage in binge eating (BE) compared with those who do not (NBE), and to analyse the relationship between eating dyscontrol and axis-I, axis-II, spectrum psychopathology using instruments that explore mood, panic-agoraphobic, social-phobic, obsessive-compulsive and eating disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Interestingly, our two groups did not differ in terms of eating restraint, a finding contrary to the results of Klatzkin et al (2015), who reported greater restraint among obese women with BED, compared with an obese non-BED group. However, our results are in line with those of Calderone et al (2015) and Herbozo, Schaefer, and Thompson (2015), who likewise found no difference between BED and non-BED obese individuals in this regard. This suggests that what leads overweight and obese individuals to restrain their eating is not the presence of BED but, rather, excess weight, a factor which is common to both groups.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our two groups did not differ in terms of eating restraint, a finding contrary to the results of Klatzkin et al (2015), who reported greater restraint among obese women with BED, compared with an obese non-BED group. However, our results are in line with those of Calderone et al (2015) and Herbozo, Schaefer, and Thompson (2015), who likewise found no difference between BED and non-BED obese individuals in this regard. This suggests that what leads overweight and obese individuals to restrain their eating is not the presence of BED but, rather, excess weight, a factor which is common to both groups.…”
Section: Discussionsupporting
confidence: 92%